Harnessing an RNA‐mediated chaperone for the assembly of influenza hemagglutinin in an immunologically relevant conformation. Issue 5 (2nd January 2018) - Yang, Seung Won; Jang, Yo Han; Kwon, Soon Bin; Lee, Yoon Jae; Chae, Wonil; Byun, Young Ho; Kim, Paul; Park, Chan; Lee, Young Jae; Kim, Choon Kang; Kim, Young Seok; Choi, Seong Il; et al.
Abstract : A novel protein‐folding function of RNA has been recognized, which can outperform previously known molecular chaperone proteins. The RNA as a molecular chaperone (chaperna) activity is intrinsic to some ribozymes and is operational during viral infections. Our purpose was to test whether influenza hemagglutinin (HA) can be assembled in a soluble, trimeric, and immunologically activating conformation by means of an RNA molecular chaperone (chaperna) activity. An RNA‐interacting domain (RID) from the host being immunized was selected as a docking tag for RNA binding, which served as a transducer for the chaperna function for de novo folding and trimeric assembly of RID‐HA1. Mutations that affect tRNA binding greatly increased the soluble aggregation defective in trimer assembly, suggesting that RNA interaction critically controls the kinetic network in the folding/assembly pathway. Immunization of mice resulted in strong hemagglutination inhibition and high titers of a neutralizing antibody, providing sterile protection against a lethal challenge and confirming the immunologically relevant HA conformation. The results may be translated into a rapid response to a new influenza pandemic. The harnessing of the novel chaperna described herein with immunologically tailored antigen‐folding functions should serve as a robust prophylactic and diagnostic tool for viral infections.—Yang, S. W., Jang, Y. H, Kwon, S. B., Lee, Y. J., Chae, W., Byun, Y. H., Kim, P., Park, C., Lee, Y J., Kim, C. K, Kim, Y. S., Choi, S. I., Seong, B. L. Harnessing an RNA‐mediated chaperone for the assembly of influenza hemagglutinin in an immunologically relevant conformation. FASEB J. 32, 2658–2675 (2018). www.fasebj.org